Visit‐to‐Visit Variability of Fasting Plasma Glucose and the Risk of Cardiovascular Disease and All‐Cause Mortality in the General Population. Issue 12 (29th November 2017) - Wang, Anxin; Liu, Xiaoxue; Xu, Jie; Han, Xiaochen; Su, Zhaoping; Chen, Shuohua; Zhang, Nan; Wu, Shouling; Wang, Yongjun; Wang, Yilong
Abstract : Background: The association of short‐term variability of fasting plasma glucose (FPG) and mortality has been well investigated. However, the relationships between visit‐to‐visit variability of FPG over longer periods of follow‐up and cardiovascular disease (CVD) and all‐cause mortality are unclear. This study aimed to investigate these relationships. Methods and Results: The current analysis included 53 607 Chinese participants (mean age, 49.10 years) who were free of CVD in the Kailuan study. Participants were divided into 4 categories by quartiles of visit‐to‐visit variability of FPG. Visit‐to‐visit variability of FPG was defined as the coefficient of variation of 3 values of FPG that were measured from the examination periods of 2006 to 2007, 2008 to 2009, and 2010 to 2011. Cox proportional hazards models were used to calculate hazard ratios and 95% confidence intervals for CVD and all‐cause mortality. After a mean follow‐up of 4.93 years, 4261 individuals developed CVD and 1545 individuals died. The incidence of CVD and all‐cause mortality was 5.04 and 5.85 per 1000 person‐years, respectively. After adjusting for mean FPG and other potential confounders, individuals in the highest quartile of variability of FPG compared with participants in the lowest quartile showed a 26% greater risk of developing CVD (hazard ratio, 1.26; 95% confidence interval, 1.08–1.47) and a 46% greater risk for all‐cause mortality (hazard ratio, 1.46; 95% confidence interval, 1.25–1.70). Conclusions: Independent of mean FPG and other baseline parameters, elevated visit‐to‐visit variability of FPG significantly increases the risk of CVD and all‐cause mortality in the general population. Measuring long‐term visit‐to‐visit variability of FPG is helpful for predicting the risk for CVD and all‐cause mortality.